Functional chitosan gel coating enhances antimicrobial properties and osteogenesis of titanium alloy under persistent chronic inflammation - Zhang, Ti; Qin, Xiaoyan; Gao, Yuan; Kong, Dan; Jiang, Yuheng; Cui, Xiang; Guo, Miantong; Chen, Junyu; Chang, Feifan; Zhang, Ming; Li, Jia; Yin, Pengbin (Frontiers in Bioengineering and Biotechnology, 2023)
Titanium is widely used as surgical bone implants due to its excellent mechanical properties, corrosion resistance, and good biocompatibility. However, due to chronic inflammation and bacterial infections caused by titanium implants, they are still at risk of failure in interfacial integration of bone implants, severely limiting their broad clinical application. In this work, chitosan gels crosslinked with glutaraldehyde were prepared and successfully loaded with silver nanoparticles (nAg) and catalase nanocapsules (n(CAT)) to achieve functionalized coating on the surface of titanium alloy steel plates. Under chronic inflammatory conditions, n(CAT) significantly reduced the expression of macrophage tumor necrosis factor (TNF-α), increased the expression of osteoblast alkaline phosphatase (ALP) and osteopontin (OPN), and enhanced osteogenesis. At the same time, nAg inhibited the growth of S. aureus and E. coli. This work provides a general approach to functional coating of titanium alloy implants and other scaffolding materials.